1997
DOI: 10.1007/s003710050109
|View full text |Cite
|
Sign up to set email alerts
|

Fast volume render techniques for interactive analysis

Abstract: General rights It is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Specifically, it was observed that vinculin was primarily localizing at the feature edge as formed by the vertical side-wall and horizontal apical surface of the silk substrates. The localization of vinculin to the feature edge was further investigated through the use of 3-dimensional (3D) surface rendering software, which creates a digital rendering of the original fluorescent signature [31]. After 3 days in culture, HCLE cells grown on patterned silk film surfaces appeared to have vinculin localized to the feature edge (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, it was observed that vinculin was primarily localizing at the feature edge as formed by the vertical side-wall and horizontal apical surface of the silk substrates. The localization of vinculin to the feature edge was further investigated through the use of 3-dimensional (3D) surface rendering software, which creates a digital rendering of the original fluorescent signature [31]. After 3 days in culture, HCLE cells grown on patterned silk film surfaces appeared to have vinculin localized to the feature edge (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…11 To enable the interactive exploration and analysis of the volume data, the renderer uses optimization schemes like adaptive ray termination, template-based viewing, adaptive progressive refinement, presence sampling, blur prevention, local volume update, and view movement. 12,13 The result is a first rendering within a second and a final volumetric display in 10 s. As the user can change visual and object parameters after each update, the response is intuitive and interactive. Note that we use volume rendering and do not display 3D graphics extracted from the volume, as with the VTK library, for example.…”
Section: Visualizationmentioning
confidence: 99%